Food consumption pattern and management of type 2 diabetic patients treated in Dschang District Hospital - Gisèle Mélanie Dongmo Agokeng; Donald Sévérin Dangang Bossi; Marc Bertrand Dandji Saah; François Ngoufack Zambou (Clinical Nutrition Open Science)
Summary: Type 2 diabetes is a global health problem with high morbidity and mortality among patients, most of whom are still economically active. The prevalence of diabetes is increasing worldwide due to changes in eating habits and a reduction of physical activities. In order to determine the level of knowledge, attitude, and practices (KAP) in nutrition in type 2 diabetic (T2D) patients treated in Dschang District Hospital (DDH), West Cameroon, a cross-sectional study was conducted in 103 type 2 diabetic patients aged between 20 and 70 years and over. A structured questionnaire was administered by an interview to collect data. The sociodemographic characteristics showed that participants of ages ranging from 40–70 years were the most affected. Among them, 59.2 % were women and 35.9 % were housewives, whereas 43.7 % were found to have a primary education level. The participants' nutritional status revealed that the prevalence of overweight and obesity was high among married patients (84.2 % and 60.0 %, respectively). It was noted from the anthropometric assessment that the prevalence of obesity among the diabetic women surveyed (77.5 %) was significantly (P < 0.05) higher than among men (22.5 %), while overweight was more prevalent in men (60.5 %). The KAP study showed that the level of education has a significant influence (P = 0.034) on diabetic nutrition practices, especially in primary and secondary level patients. The eating habits of patients confirmed these poor KAP with irregular consumption of fresh fruits and vegetables and daily restriction of basic foods. This investigation highlights the need to promote education in all social strata, with particular emphasis on nutritional education among housewives, where the prevalence of diabetes was highest.